Calculating disability-adjusted life years (DALY) as a measure of excess cancer risk following radiation exposure. (12th October 2015) - Shimada, K; Kai, M
Abstract: This paper has proposed that disability-adjusted life year (DALY) can be used as a measure of radiation health risk. DALY is calculated as the sum of years of life lost (YLL) and years lived with disability (YLD). This multidimensional concept can be expressed as a risk index without a probability measure to avoid the misuse of the current radiation detriment at low doses. In this study, we calculated YLL and YLD using Japanese population data by gender. DALY for all cancers in Japan per 1 Gy per person was 0.84 year in men and 1.34 year in women. The DALY for all cancers in the Japanese baseline was 4.8 in men and 3.5 in women. When we calculated the ICRP detriment from the same data, DALYs for the cancer sites were similar to the radiation detriment in the cancer sites, excluding leukemia, breast and thyroid cancer. These results suggested that the ICRP detriment overestimate the weighting fraction of leukemia risk and underestimate the weighting fraction of breast and thyroid cancer. A big advantage over the ICRP detriment is that DALY can calculate the risk components for non-fatal diseases without the data of lethality. This study showed that DALY is a practical tool that can compare many types of diseases encountered in public health.